One is all, all is one? Embracing value-driven approaches in research assessment for a resilient academic future (PUBMET, 2025)
In recent years, the call to reform research assessment has gained significant momentum, driven by a growing recognition that the current systems often fail to align with the original mission of universities. We see an ever broadening consensus worldwide to build alternatives for evaluation systems that are entangled in a productivity-driven culture, prioritising the simplistic use of bibliometrics and prestige over the integrity, quality, and broader impact of scholarly work.